KONSULTASI PUBLIK KAJIAN PERFORMANCE DALAM RANGKA OPTIMALISASI PEMBANGUNAN PARIWISATA DI KOTA TUAL - Ega, La; Irwanto, Irwanto; Boreel, Aryanto; Sinay, Lexy J.; Tupan, Johan M.; Ferdinandus, Stenly Jacobus; Faisal, Muhammad; Wenno, Meiske; Regar, Erfendi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
Sustainable tourism development requires careful planning and involves various stakeholders. This community service activity aims to conduct public consultation on tourism development performance study in Tual City. The activity was carried out on December 3, 2024, involving 35 participants from various Regional Government Organizations (OPD), related institutions, and tourism business actors. The methods used were Focus Group Discussion (FGD) and presentation of study results. The consultation results show that Tual City has great marine ecotourism potential with a vision to become a sustainable marine ecotourism and cultural destination. SWOT analysis identified weaknesses in tourism facilities and basic infrastructure that need improvement. The strategic recommendations include infrastructure improvement, destination strengthening, human resource training, and tourism institutional strengthening. This public consultation successfully produced a comprehensive strategy for optimizing sustainable tourism development in Tual City involving all relevant stakeholders.